Hollow Polymer Particles: A Review - Ros Azlinawati, Ramli (Royal Society of Chemistry, 2017)
Herein, the basic principles, such as the definitions, classifications, and properties, of hollow polymer particles (HPPs) are critically investigated. HPP preparation methods, such as template, self-assembly, and acid/alkali swelling methods, have been briefly introduced. Moreover, advanced methods to prepare HPPs have been highlighted. In addition, recent studies and applications of HPPs have been briefly described. HPPs are polymeric spheres with size in the range from nanometer to micron and a single pore inside the particles. This review is focused on the classification of HPPs based on the core–shell, single particles, and stimuli-responsiveness. A single pore structure is the most desirable characteristic that allows this class of polymers to encapsulate large guest molecules and thus to be used as a drug delivery system.